Public Relations Strategy in Improving Cinema Company Reputation (Case Study Cinema21) - Karina Khairunnisa Safitri; Putri Sonya; Nico Wattimena (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Human beings needs to fulfill their life, entertainment is one of them. In this era of digitalization there are various form of enrtainment, one of them is cinema. CINEMA 21’s is the largest and vast growing group of cinemas in Indonesia with many branches nationwide. CINEMA 21 public relations always try to improve their reputation by providing best facilities to its customers. The purpose of this research, is to analyze CINEMA 21’s public relations activities to improve their reputation. The research method used is qualitative descriptive with primary data collection conducted through in-depth interviews with internal and external corporate sources, while secondarydata through company data (Company Profile), books, Internet (Articles) and Websites. The results of this research found that CINEMA 21’s public relations activities managed to maintain the company’s reputation.